Exploring the Food Waste Produced by Youth: a Case Study in DKI Jakarta - Christania Paruntu; Zakianis Zakianis (Journal of Social Research, 2023)
Young people are a vulnerable group in disposing of food waste due to the spontaneity of this group. This study aims to explore food waste generated by young people with case studies in DKI Jakarta starting from planning and shopping for food, cooking food, storing and evaluating food, the types of food waste that usually arise up to the stage of processing food waste. This type of research is exploratory qualitative. Research data collection method is semi-structured in-depth interviews with the determination of informants using purposive sampling method. Based on the results of in-depth interviews, the average informant tends to have the potential to generate food waste at every stage starting from planning and shopping for food, cooking of food and storage and grading of food. The types of food waste that usually arise are avoidable waste such as rice, edible fruit peels and edges of bread as well as unavoidable food waste such as fish bones and fruit skins that cannot be consumed. The majority of informants still throw away leftover food waste without prior sorting because there are no supporting facilities for waste sorting. In conclusion, there are still many young people who throw away food waste because they do not plan meals regularly and cook food in more portions, the food waste is on average not sorted and not processed before being disposed of. edible fruit peels and bread crusts as well as unavoidable food waste such as fish bones and fruit skins that cannot be consumed. The majority of informants still throw away leftover food waste without prior sorting because there are no supporting facilities for waste sorting. In conclusion, there are still many young people who throw away food waste because they do not plan meals regularly and cook food in more portions, the food waste is on average not sorted and not processed before being disposed of. edible fruit peels and bread crusts as well as unavoidable food waste such as fish bones and fruit skins that cannot be consumed. The majority of informants still throw away leftover food waste without prior sorting because there are no supporting facilities for waste sorting. In conclusion, there are still many young people who throw away food waste because they do not plan meals regularly and cook food in more portions, the food waste is on average not sorted and not processed before being disposed of.